(untitled) (Global Journal of Management and Business Research, 2021)
This paper investigates the still evolving strategic trajectories and the context adopted for the procedures for inducting a Least Risk Bomb Location (LRBL) that began with discretionary participation by various aircraft manufacturers approximately in the year 1972, where the use of a specific procedure has been designed to decrease the effects of an explosion significantly in the aircraft#x2019;s passenger cabins of large commercial airplanes. Additionally, the International Civil Aviation Organization (ICAO) has provided the information on the location of the LRBL and guidance to various operators (National/International) on the procedures to use when a suspected threat item is found on-board an airplane. The designation of LRBL for aero planes is intended to be used solely for the transport of cargo, where an aero plane must include a designated location where a bomb or other explosive device could be designated to protect integrity of the structure and flight-critical systems from damage in the case of detonation occurs.